METAPHORS IN THE EX-GAM'S POLITICAL DISCOURSES DURING PRE-PUBLIC ELECTIONS IN ACEH - Jarjani Usman (Universitas Islam Negeri Banda Aceh, 2017)
The Free Aceh Movement, locally called Gerakan Aceh Merdeka (GAM), developed several unique political discourses after having signed a peace accord with the Government of Indonesia (GoI) in Helsinki in 2005. The discourses created are metaphorical in Acehnese language, aimed to structure people's mind and to be accepted and transformed into their actions that supported GAM during pre-public election post conflicts. However, research on analyzing the metaphors is scant. This research used Lakoff and Johnson's (1980a, 1980b) conceptual metaphor and Fairclough's framework of Critical Discourse Analysis (CDA) to critically analyze the political discourses in order to unveil the meaning and their ideology position. The research shows the most commonly used metaphor was ELECTION IS A BATTLE. However, the currently used political metaphors are more persuasive, urging people to voluntarily come back to their political party, than previously used ones that seemed to strongly force people to be on their side.